Towards mobility management in next-generation wireless systems networks from a multi-objective perspective - Ismail, Adzrool Idzwan bin; Ismail, Mohd Amirul Helmi; Ismail, Izwah (International Journal of Innovative Research and Scientific Studies, 2025)
The rapid expansion of mobile applications and consumer demand for uninterrupted connectivity necessitate advancements in mobility management within next-generation wireless networks. This paper evaluates various mobility management protocols, including satellite networks, wireless asynchronous transfer mode (ATM), mobile Internet Protocol (IP), and public land mobile networks (PLMN). Through a comprehensive multi-objective analysis, we explore the integration and comparative effectiveness of these protocols. Our findings indicate distinct performance trade-offs among mobility management strategies. Specifically, strategies based on registration areas outperform those utilizing reporting cells, except in scenarios characterized by high paging costs. Moreover, we demonstrate that various paging methods excel in different regions of the objective space, with blanket paging consistently identified as the least efficient. The improvements in network design technologies notably enhance the capabilities of mobile graphy, facilitating higher-quality multimedia streaming, quicker processing of high-resolution content, and better utilization of mobile graphy hardware such as advanced camera sensors and graphics processors. This study guides network operators and mobile graphy practitioners in selecting optimal strategies aligned with their specific operational requirements, highlighting unresolved issues critical to future network evolution.